INTERACTION AND EFFICIENCY OF DIGITAL SIGNAL TRANSMISSION SYSTEMS - Khudoyberganov Shavkat Karimovich (Web of Journals Publishing, 2024)
The effectiveness of the use of the digital communication system spectrum (frequency band), two modulation types – phase modulated (PM) and quadratic AMLP, the potential interference of the types of modulation signals, the most used types of modulation in digital television systems based on the use of one or more carrier frequencies are considered. For the types of modulation used in digital communication systems, methods for determining real (real) spectral efficiency are presented, the dependence of the probability of error in coherent reception on the signal/interference ratio is analyzed.
Keywords: Digital communication, modulation, digital TV, signal, frequency, range, amplitude-phase, error reception.